Long non-coding RNAs in the pathogenesis of heart failure: A literature review - Fan, Xiaoyan; Zhang, Zhenwei; Zheng, Liang; Wei, Wei; Chen, Zetao (Frontiers in Cardiovascular Medicine, 2022)
Heart failure (HF) is a common cardiovascular disorder and a major cause of mortality and morbidity in older people. The mechanisms underlying HF are still not fully understood, restricting novel therapeutic target discovery and drug development. Besides, few drugs have been shown to improve the survival of HF patients. Increasing evidence suggests that long non-coding RNAs (lncRNAs) serve as a critical regulator of cardiac physiological and pathological processes, regarded as a new target of treatment for HF. lncRNAs are versatile players in the pathogenesis of HF. They can interact with chromatin, protein, RNA, or DNA, thereby modulating chromatin accessibility, gene expressions, and signaling transduction. In this review, we summarized the current knowledge on how lncRNAs involve in HF and categorized them into four aspects based on their biological functions, namely, cardiomyocyte contractility, cardiac hypertrophy, cardiac apoptosis, and myocardial fibrosis. Along with the extensive laboratory data, RNA-based therapeutics achieved great advances in recent years. These indicate that targeting lncRNAs in the treatment of HF may provide new strategies and address the unmet clinical needs.